Family farms in the EU – their structural and economic diversity and opportunities of growth - Poczta, Walenty; Szuba-Barańska, Ewelina; Beba, Patrycja; Czubak, Wawrzyniec (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2015)
This paper identifies criteria for defining family farms on the basis of state of the art: definitions for family farms, published in literature.In order to isolate the family farm from the entire population of farms in the EU it has been assumed that the farm should be owned by an individual farmer, it should be the primary place of work and source of income.For the research purposes two levels of farm income per full-time paid employees were examined: income corresponding to the net minimum wage in the country, and average monthly gross wages and salaries. To identify the number of family farms in the EU and the resources they control, both Eurostat and FADN databases were used.In the EU there are 12 million agricultural holdings, including a 11.7 million private farms. Based on the criteria of delimitation, family farms (3.6 million) account for 30% of the total number of farms. They possess more than half (88.3 million hectares) of the agricultural land resource of the European Union. Family farms employ approximately 64% (4.9 million) of the family work units (FWU) and generated 54% (164.7 million) of total agricultural production.This separated group of farms is the potential for development of family farming.
Keywords: family farms; criteria of defining; significance and opportunities of development of family farms